Great myths of the brain - Jarrett, Christian (Great myths of psychology., 2015)
This book introduces readers to the field of neuroscience by examining popular myths about the human brain. The book explores commonly-held myths of the brain through the lens of scientific research, backing up claims with studies and other evidence. "Do we only use 10% of our brain?", "pregnant women lose their mind", "right-brained people are more creative," and other questions and claims are addressed. The book also delves into myths relating to specific brain disorders, including epilepsy, autism, and dementia